Impact of environmental hygiene interventions on healthcare-associated infections and patient colonization: a systematic review - Aljahdali, Fahad Hameed; Sahly, Tariq Naif; Hinkish, Faisal Mohammed Behais; al ghamdi, Moufaq abdullah sultan; Almalki, Yousef Dhayfallah Hamdan; ALYAhYahywy, Abdullah Shami; Alawi, Ali Thabit Mohammed; Albeladi, Abdullah Obaid; ALJOFI, MOHAMMED OMAR JAHNI; Aleryani, Ali Jaber; et al. (Journal of Posthumanism, 2024)
Background: Healthcare-associated infections (HAIs) are an important concern in medical settings, as they can increase patient morbidity and mortality, prolong hospital stays, and escalate healthcare costs. Environmental hygiene and cleaning play a crucial role in controlling these infections, particularly in avoiding the spread of multidrug-resistant organisms (MDROs).Aim: To investigate the effect of environmental hygiene interventions on HAIs & case colonization. Patients and methods: This systematic review followed PRISMA guidelines, searching PubMed, Embase, Cochrane Library, Web of Science, & Scopus without date or language restrictions. Inclusion criteria encompassed RCTs, prospective cohorts, and before-after studies evaluating hygiene interventions in healthcare settings, focusing on HAIs, colonization, and microbial burden. Risk of bias has been evaluated utilizing the Cochrane RoB tool. Results: From 635 records, 8 studies (3 RCTs, 5 before-after) were included, involving mechanical (e.g., pulsed-xenon UV, filters), chemical (e.g., copper surfaces, hydrogen peroxide), and human factors interventions. Over half demonstrated significant reductions in HAIs or colonization (e.g., MRSA, VRE, C. difficile), with many reducing environmental bioburden. Heterogeneity in designs, microorganisms, and controls limited meta-analysis; most studies were high quality but lacked true controls. Conclusion: Environmental hygiene interventions effectively reduce HAIs and colonization, particularly for environmentally persistent pathogens like VRE. However, study variability underscores the need for standardized, multicenter RCTs to strengthen evidence and guide infection control policies.